Keefektifan Bahan Ajar Unit Kegiatan Belajar Mandiri (UKBM) Teks Esksplanasi Berbasis Literasi untuk Siswa Kelas XI MAN 3 Kediri - Ucik Nurmawati; Heny Sulistyowati (Journal on Education, 2023)
This study aims to test the effectiveness of UKBM teaching materials Literacy-Based Explanatory Text for Class XI Students of MAN 3 Kediri. The type of research used in this research is experimental research with the Pre-Experimental Design research with the One-Group Pretest-Posttest Design model. The subjects of this study were 34 students of class XI Religion 2 MAN 3. Data collection methods used are tests, questionnaires, documentation, and observation. Meanwhile, to analyze the data using the effectiveness test. The results showed that the average pretest score was 69.24 and the posttest average score was 80.24. This means that student learning outcomes have increased by 14.28, and the average gain test is included in the moderate criteria, which is equal to 0.36 or 36%. Based on the explanation above, the use of UKBM teaching materials is effectively used to improve students' literacy skills in learning explanatory texts for class XI MAN 3 Kediri.